Maximizing the Role of Parents Through Religious Education in the Family in the Scope of Early Childhood Education - Demsy Jura; Cherly L. N. Naray (STAI Hubbulwathan Duri, 2023)
Religious education for early childhood in the family environment needs to be carried out properly and responsibly because it is during an important period in the child's growth period (The Golden Age). Active parental participation needs to be maximized so that it makes a significant contribution to the child's spiritual growth. This study aims to see how parents can maximize their role in early childhood education through religious education in the family. This research was carried out using a descriptive qualitative approach. This study comprises a comprehensive examination of relevant scholarly articles through a literature review. A total of 30 journal papers published between 2010 and 2023 were gathered for the literature review. According to the findings of the review, it is established that the results of this study found that the implementation of education, especially religious education, must be a major concern. This is because children are quite vulnerable to the environment around them so the role of parents in guiding religious aspects becomes very important.